SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A phase I clinical study to evaluate rapid, high-volume, subcutaneous auto-injector tolerability with recombinant human hyaluronidase - David W. Kang; Robert J. Connor; Tara Nekoroski; Jo Ann M. Bitsura; Susan K. Kindig; Stephen P. Knowles; Michael J. LaBarre (Drug Delivery and Translational Research, 2026)
Until recently, approved handheld auto-injectors (AIs) have been limited to volumes ≤ 2 mL. A prototype rapid high-volume AI (HVAI) that can deliver 10 mL in 30 s was developed to administer therapeutics co-formulated with a proprietary recombinant human hyaluronidase PH20 (rHuPH20). This phase I, open-label study assessed the tolerability of subcutaneous (SC) injections of 10% (100 mg/mL) immunoglobulin G (IgG) solution co-administered with 4000 U/mL rHuPH20, delivered using a syringe pump at a target rate of 5 or 10 mL/30 seconds or the prototype HVAI at a target rate of 10 mL/30 seconds in healthy human subjects. Subjects received 5 mL (Cohort A, n = 12) or 10 mL (Cohort B, n = 12) of test solution via syringe pump (injection visit 1), and 10 mL of test solution via HVAI (Cohorts A & B; injection visit 2). Primary endpoints were tolerability and safety outcomes. Secondary endpoints included HVAI injection duration. All 24 subjects completed visit 1; 23/24 completed visit 2. All injections were tolerated, with no serious adverse events (AEs). Following syringe pump administration, 6/24 subjects (25%) reported eight treatment-emergent AEs (TEAEs); after HVAI administration, 4/23 (17%) reported four TEAEs, all mild in severity. Mean (± SEM) injection duration via HVAI was 27.9 ± 0.8 s. Most subjects (91%, 21/23) experienced no or mild injection-site pain following HVAI administration, and 96% (22/23) said they would be willing to have the HVAI injection again. SC injection of a 10% IgG solution in combination with rHuPH20 was well tolerated at an injection rate of 10 mL/~30 s using the prototype HVAI.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Microfluidics for protein interaction studies: current methods, challenges, and future perspectives - Matthias M. Schneider; Tuomas P. J. Knowles; Sandro Keller; Georg Krainer (European Biophysics Journal, 2025)
Proteins are the key molecular players of life, carrying out their functions through interactions. Microfluidic technologies have emerged as powerful tools for studying protein interactions with exquisite sensitivity, resolution, and throughput. In this review, we highlight recent advances in microfluidic approaches for protein interaction studies. We first explore continuous-flow microfluidics, which utilize diffusion-based techniques and electrophoretic methods, before examining the role of droplet microfluidics in probing protein interactions. We provide an overview of the diverse applications of these technologies in biophysical research, drug discovery, and clinical diagnostics. We conclude with a discussion of the potential of microfluidics for driving future innovations and emerging opportunities.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Detection of foot-and-mouth disease viruses from the A/AFRICA/G-I genotype in the Sultanate of Oman - Wafa Ahmed Al-Rawahi; Elshafie Ibrahim Elshafie; Senan Baqir; Aliya Al-Ansari; Jemma Wadsworth; Hayley M. Hicks; Nick J. Knowles; Antonello Di Nardo; Donald P. King; Stephan Zientara; Fajer Al Salloom; Abraham Sangula; et al. (Preventive Veterinary Medicine, 2024)

Experiences of and support for black women in ecology, evolution, and marine science - Nikki Traylor-Knowles; Anamica Bedi de Silva; Anjali D. Boyd; Karlisa A. Callwood; Alexandra C. D. Davis; Giselle Hall; Victoria Moreno; Cinda P. Scott (Frontiers in Marine Science, 2023)
Systemic racism and sexism are well documented in ecology, evolution, and marine science. To combat this, institutions are making concerted efforts to recruit more diverse people by focusing on the recruitment of Black people. However, despite these initiatives, white supremacy culture still prevails. The retention of Black people in ecology, evolution, and marine science has not increased in the ways that were hoped for. This is particularly true for Black women, who struggle to find a safe working environment that values their contributions and allows them to openly celebrate their own culture and identity. In this perspective article, we discuss the challenges that Black women face every day, and the needs of Black women to thrive in ecology, evolution, and marine science. We have written this directly to Black women and provide information on not only our challenges, but our stories. However, readers of all identities are welcome to listen and examine their role in perpetuating systemic racism and sexism. Lastly, we discuss support mechanisms for navigating ecology, evolution, and marine science spaces so that Black women can thrive.

Interannual variability of spring and summer monsoon growing season carbon exchange at a semiarid savanna over nearly two decades - Russell L. Scott; Miriam R. Johnston; John F. Knowles; Natasha MacBean; Kashif Mahmud; Matt C. Roby; Matthew P. Dannenberg (Agricultural and Forest Meteorology, 2023)

Bark beetle impacts on forest evapotranspiration and its partitioning - John F. Knowles; Nels R. Bjarke; Andrew M. Badger; Max Berkelhammer; Joel A. Biederman; Peter D. Blanken; Mario Bretfeld; Sean P. Burns; Brent E. Ewers; John M. Frank; Jeffrey A. Hicke; Leanne Lestak; et al. (Science of The Total Environment, 2023)

Direct 14C dating of equine products preserved in archaeological pottery vessels from Botai and Bestamak, Kazakhstan - Emmanuelle Casanova; Timothy D. J. Knowles; Alan K. Outram; Natalie A. Stear; Mélanie Roffet-Salque; Viktor Zaibert; Andrey Logvin; Irina Shevnina; Richard P. Evershed (Archaeological and Anthropological Sciences, 2022)
Direct and accurate radiocarbon dating of lipid residues preserved in ceramics is a recently established method that allows direct dating of specific food products and their inception in human subsistence strategies. The method targets individual fatty acids originating from animal fats such as ruminant dairy, ruminant adipose, non-ruminant adipose and aquatic fats. Horse lipid residues found in Central Asian pottery vessels are also directly dateable using this new method. Here we present the identification of equine lipid residues preserved in two pottery assemblages from the Neolithic and Eneolithic in Kazakhstan and their direct 14 C dating. The site of Botai, previously radiocarbon-dated to the 4th millennium BC, was used as a reference to evaluate the dates obtained directly on horse lipids. The direct dating of equine products extracted from Botai potsherds are shown to be compatible with previous 14 C dates at the site. The site of Bestamak, lacking previous 14 C measurements, had been relatively dated to the Neolithic based on pottery typologies. The direct dating of equine residues made it possible to anchor the pottery assemblage of Bestamak in the 6th millennium BC confirming their Neolithic attribution. These findings demonstrate the potential for dating horse products through a compound-specific approach, while highlighting challenges in 14 C dating individual fatty acids from lipid extracts in which their abundances differ substantially.

Exceptional heat and atmospheric dryness amplified losses of primary production during the 2020 U.S. Southwest hot drought - Matthew P. Dannenberg; Dong Yan; Mallory L. Barnes; William K. Smith; Miriam R. Johnston; Russell L. Scott; Joel A. Biederman; John F. Knowles; Xian Wang; Tomer Duman; Marcy E. Litvak; John S. Kimball; et al. (Global Change Biology, 2022)
Earth's ecosystems are increasingly threatened by “hot drought,” which occurs when hot air temperatures coincide with precipitation deficits, intensifying the hydrological, physiological, and ecological effects of drought by enhancing evaporative losses of soil moisture (SM) and increasing plant stress due to higher vapor pressure deficit (VPD). Drought‐induced reductions in gross primary production (GPP) exert a major influence on the terrestrial carbon sink, but the extent to which hotter and atmospherically drier conditions will amplify the effects of precipitation deficits on Earth's carbon cycle remains largely unknown. During summer and autumn 2020, the U.S. Southwest experienced one of the most intense hot droughts on record, with record‐low precipitation and record‐high air temperature and VPD across the region. Here, we use this natural experiment to evaluate the effects of hot drought on GPP and further decompose those negative GPP anomalies into their constituent meteorological and hydrological drivers. We found a 122 Tg C (>25%) reduction in GPP below the 2015–2019 mean, by far the lowest regional GPP over the Soil Moisture Active Passive satellite record. Roughly half of the estimated GPP loss was attributable to low SM (likely a combination of record‐low precipitation and warming‐enhanced evaporative depletion), but record‐breaking VPD amplified the reduction of GPP, contributing roughly 40% of the GPP anomaly. Both air temperature and VPD are very likely to continue increasing over the next century, likely leading to more frequent and intense hot droughts and substantially enhancing drought‐induced GPP reductions.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Pre-exposure to a variable temperature treatment improves the response of Acropora cervicornis to acute thermal stress - Allyson DeMerlis; Amanda Kirkland; Madeline L. Kaufman; Anderson B. Mayfield; Nathan Formel; Graham Kolodziej; Derek P. Manzello; Diego Lirman; Nikki Traylor-Knowles; Ian C. Enochs (Coral Reefs, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Montane forest productivity across a semiarid climatic gradient - John F. Knowles; Russell L. Scott; Joel A. Biederman; Peter D. Blanken; Sean P. Burns; Sabina Dore; Thomas E. Kolb; Marcy E. Litvak; Greg A. Barron‐Gafford (Global Change Biology, 2020)
High‐elevation montane forests are disproportionately important to carbon sequestration in semiarid climates where low elevations are dry and characterized by low carbon density ecosystems. However, these ecosystems are increasingly threatened by climate change with seasonal implications for photosynthesis and forest growth. As a result, we leveraged eddy covariance data from six evergreen conifer forest sites in the semiarid western United States to extrapolate the status of carbon sequestration within a framework of projected warming and drying. At colder locations, the seasonal evolution of gross primary productivity (GPP) was characterized by a single broad maximum during the summer that corresponded to snow melt‐derived moisture and a transition from winter dormancy to spring activity. Conversely, winter dormancy was transient at warmer locations, and GPP was responsive to both winter and summer precipitation such that two distinct GPP maxima were separated by a period of foresummer drought. This resulted in a predictable sequence of primary limiting factors to GPP beginning with air temperature in winter and proceeding to moisture and leaf area during the summer. Due to counteracting winter (positive) and summer (negative) GPP responses to warming, leaf area index and moisture availability were the best predictors of annual GPP differences across sites. Overall, mean annual GPP was greatest at the warmest site due to persistent vegetation photosynthetic activity throughout the winter. These results indicate that the trajectory of this region's carbon sequestration will be sensitive to reduced or delayed summer precipitation, especially if coupled to snow drought and earlier soil moisture recession, but summer precipitation changes remain highly uncertain. Given the demonstrated potential for seasonally offsetting responses to warming, we project that decadal semiarid montane forest carbon sequestration will remain relatively stable in the absence of severe disturbance.

A vaccine-matching assessment of different genetic variants of serotype O foot-and-mouth disease virus isolated in Ethiopia between 2011 and 2014 - Yeneneh Tesfaye; Fazlurrahman Khan; Martha Yami; Jemma Wadsworth; Nick J. Knowles; Donald P. King; Esayas Gelaye (Archives of Virology, 2020)

Correction to: Recommendations for the nomenclature of enteroviruses and rhinoviruses - P. Simmonds; A. E. Gorbalenya; H. Harvala; T. Hovi; N. J. Knowles; A. M. Lindberg; M. S. Oberste; A. C. Palmenberg; G. Reuter; T. Skern; C. Tapparel; K. C. Wolthers; et al. (Archives of Virology, 2020)
Unfortunately, one of the affiliations of author “A. E. Gorbalenya” was missed in original version. The affiliation is updated here.

Microfluidic approaches for the analysis of protein–protein interactions in solution - William E. Arter; Aviad Levin; Georg Krainer; Tuomas P. J. Knowles (Biophysical Reviews, 2020)
Exploration and characterisation of the human proteome is a key objective enabling a heightened understanding of biological function, malfunction and pharmaceutical design. Since proteins typically exhibit their behaviour by binding to other proteins, the challenge of probing protein-protein interactions has been the focus of new and improved experimental approaches. Here, we review recently developed microfluidic techniques for the study and quantification of protein–protein interactions. We focus on methodologies that utilise the inherent strength of microfluidics for the control of mass transport on the micron scale, to facilitate surface and membrane-free interrogation and quantification of interacting proteins. Thus, the microfluidic tools described here provide the capability to yield insights on protein–protein interactions under physiological conditions. We first discuss the defining principles of microfluidics, and methods for the analysis of protein–protein interactions that utilise the diffusion-controlled mixing characteristic of fluids at the microscale. We then describe techniques that employ electrophoretic forces to manipulate and fractionate interacting protein systems for their biophysical characterisation, before discussing strategies that use microdroplet compartmentalisation for the analysis of protein interactions. We conclude by highlighting future directions for the field, such as the integration of microfluidic experiments into high-throughput workflows for the investigation of protein interaction networks.

RAD-Seq Analysis and in situ Monitoring of Nassau Grouper Reveal Fine-Scale Population Structure and Origins of Aggregating Fish - Krista D. Sherman; Josephine R. Paris; Robert Andrew King; Karen A. Moore; Craig P. Dahlgren; Lindy C. Knowles; Kristine Stump; Charles R. Tyler; Jamie R. Stevens (Frontiers in Marine Science, 2020)

Recommendations for the nomenclature of enteroviruses and rhinoviruses - P. Simmonds; A. E. Gorbalenya; H. Harvala; T. Hovi; N. J. Knowles; A. M. Lindberg; M. S. Oberste; A. C. Palmenberg; G. Reuter; T. Skern; C. Tapparel; K. C. Wolthers; et al. (Archives of Virology, 2020)
Enteroviruses (EVs) and rhinoviruses (RVs) are significant pathogens of humans and are the subject of intensive clinical and epidemiological research and public health measures, notably in the eradication of poliovirus and in the investigation and control of emerging pathogenic EV types worldwide. EVs and RVs are highly diverse in their antigenic properties, tissue tropism, disease associations and evolutionary relationships, but the latter often conflict with previously developed biologically defined terms, such as “coxsackieviruses”, “polioviruses” and “echoviruses”, which were used before their genetic interrelationships were understood. This has created widespread formatting problems and inconsistencies in the nomenclature for EV and RV types and species in the literature and public databases. As members of the International Committee for Taxonomy of Viruses (ICTV) Picornaviridae Study Group, we describe the correct use of taxon names for these viruses and have produced a series of recommendations for the nomenclature of EV and RV types and their abbreviations. We believe their adoption will promote greater clarity and consistency in the terminology used in the scientific and medical literature. The recommendations will additionally provide a useful reference guide for journals, other publications and public databases seeking to use standardised terms for the growing multitude of enteroviruses and rhinoviruses described worldwide.

Testing main Amazonian rivers as barriers across time and space within widespread taxa - Renata M. Pirani; Fernanda P. Werneck; Andréa T. Thomaz; Mariah L. Kenney; Marcelo J. Sturaro; Teresa C. S. Ávila‐Pires; Pedro L. V. Peloso; Miguel T. Rodrigues; L. Lacey Knowles (Journal of Biogeography, 2019)
Aim Present Amazonian diversity patterns can result from many different mechanisms and, consequently, the factors contributing to divergence across regions and/or taxa may differ. Nevertheless, the river‐barrier hypothesis is still widely invoked as a causal process in divergence of Amazonian species. Here we use model‐based phylogeographic analyses to test the extent to which major Amazonian rivers act similarly as barriers across time and space in two broadly distributed Amazonian taxa. Local Amazon rain forest. Taxon The lizard Gonatodes humeralis (Sphaerodactylidae) and the tree frog Dendropsophus leucophyllatus (Hylidae). Methods We obtained RADseq data for samples distributed across main river barriers, representing main Areas of Endemism previously proposed for the region. We conduct model‐based phylogeographic and genetic differentiation analyses across each population pair. Results Measures of genetic differentiation (based on F ST calculated from genomic data) show that all rivers are associated with significant genetic differentiation. Parameters estimated under investigated divergence models showed that divergence times for populations separated by each of the 11 bordering rivers were all fairly recent. The degree of differentiation consistently varied between taxa and among rivers, which is not an artifact of any corresponding difference in the genetic diversities of the respective taxa, or to amounts of migration based on analyses of the site‐frequency spectrum. Main conclusions Taken together, our results support a dispersal (rather than vicariance) history, without strong evidence of congruence between these species and rivers. However, once a species crossed a river, populations separated by each and every river have remained isolated—in this sense, rivers act similarly as barriers to any further gene flow. This result suggests differing degrees of persistence and gives rise to the seeming contradiction that the divergence process indeed varies across time, space and species, even though major Amazonian rivers have acted as secondary barriers to gene flow in the focal taxa.

A Rabbit Model for Sheep-Associated Malignant Catarrhal Fever Research: from Virus Infection to Pathogenesis Studies and Vaccine Development - Cristina W. Cunha; Donal O’Toole; Naomi S. Taus; Smriti Shringi; Donald P. Knowles; Hong Li (Current Clinical Microbiology Reports, 2019)

Foot-and-mouth disease in Southern Ghana: occurrence and molecular characterization of circulating viruses - Mathias V. Teye; Teresa K. Sebunya; Elliot M. Fana; Donald P. King; LaToya Seoke; Nick J. Knowles; Joseph A. Awuni; George Matlho; Melvin Leteane; Joseph M. K. Hyera (Tropical Animal Health and Production, 2019)

Biochemical diversity of glycosphingolipid biosynthesis as a driver of Coccolithovirus competitive ecology - Jozef I. Nissimov; David Talmy; Liti Haramaty; Helen F. Fredricks; Ehud Zelzion; Ben Knowles; A. Murat Eren; Rebecca Vandzura; Christien P. Laber; Brittany M. Schieler; Christopher T. Johns; Kuldeep D. More; et al. (Environmental Microbiology, 2019)
Summary Coccolithoviruses (EhVs) are large, double‐stranded DNA‐containing viruses that infect the single‐celled, marine coccolithophore Emiliania huxleyi . Given the cosmopolitan nature and global importance of E. huxleyi as a bloom‐forming, calcifying, photoautotroph, E. huxleyi –EhV interactions play a key role in oceanic carbon biogeochemistry. Virally‐encoded glycosphingolipids (vGSLs) are virulence factors that are produced by the activity of virus‐encoded serine palmitoyltransferase (SPT). Here, we characterize the dynamics, diversity and catalytic production of vGSLs in an array of EhV strains in relation to their SPT sequence composition and explore the hypothesis that they are a determinant of infectivity and host demise. vGSL production and diversity was positively correlated with increased virulence, virus replication rate and lytic infection dynamics in laboratory experiments, but they do not explain the success of less‐virulent EhVs in natural EhV communities. The majority of EhV‐derived SPT amplicon sequences associated with infected cells in the North Atlantic derived from slower infecting, less virulent EhVs. Our lab‐, field‐ and mathematical model‐based data and simulations support ecological scenarios whereby slow‐infecting, less‐virulent EhVs successfully compete in North Atlantic populations of E. huxleyi , through either the preferential removal of fast‐infecting, virulent EhVs during active infection or by having access to a broader host range.

Evolution of the latitudinal diversity gradient in the hyperdiverse ant genus Pheidole - Evan P. Economo; Jen‐Pan Huang; Georg Fischer; Eli M. Sarnat; Nitish Narula; Milan Janda; Benoit Guénard; John T. Longino; L. Lacey Knowles (Global Ecology and Biogeography, 2019)
Aim The latitudinal diversity gradient is the dominant geographic pattern of life on Earth, but a consensus understanding of its origins has remained elusive. The analysis of recently diverged, hyper‐rich invertebrate groups provides an opportunity to investigate latitudinal patterns with the statistical power of large trees while minimizing potentially confounding variation in ecology and history. Here, we synthesize global phylogenetic and macroecological data on a hyperdiverse (> 1,100 species) ant radiation, Pheidole and test predictions of three general explanations for the latitudinal gradient: variation in diversification rates, tropical conservatism and ecological regulation. Location Global. Time period The past 35 million years. Major taxa studied The hyperdiverse ant genus Pheidole Westwood. Methods We assembled geographic data for 1,499 species and morphospecies, and inferred a dated phylogeny for 449 species of Pheidole , including 167 species newly sequenced for this study. We tested for correlations between diversification rate and latitude with Bayesian analysis of macroevolutionary mixtures (BAMM), hidden state speciation and extinction (HiSSE), geographic state speciation and extinction (GeoSSE), and a non‐parametric method (FiSSE), evaluated evidence for richness steady state, and examined patterns of diversification as Pheidole spread around the globe. Results There was no evidence of systematic variation of net diversification rates with latitude across any of the methods. We found that Pheidole diversification occurred in bursts when new continents were colonized, followed by a slowdown in each region, but there is no evidence richness has saturated at an equilibrium in any region. Additionally, we found latitudinal affinity is moderately conserved with a Neotropical ancestor and simulations show that phylogenetic inertia alone is sufficient to produce the gradient pattern. Main conclusions Our results provide no evidence that diversification rates vary systematically with latitude. Richness is far from steady state in each region, contrary to the ecological regulation hypothesis, although there is evidence that ecological opportunity promotes diversification after colonization of new areas. The fact that niche conservatism is strong enough to produce the gradient pattern is in accord with the tropical conservatism hypothesis. Overall, these results shed light on the mechanisms underlying the emergence of the diversity gradient within the past 34 million years, complementing recent work on deeper time‐scales, and more generally contribute toward much‐needed invertebrate perspective on global biodiversity dynamics.

Evolving in isolation: Genetic tests reject recent connections of Amazonian savannas with the central Cerrado - Luciana C. Resende‐Moreira; L. Lacey Knowles; Andréa T. Thomaz; Joyce R. Prado; Andrea P. Souto; José P. Lemos‐Filho; Maria Bernadete Lovato (Journal of Biogeography, 2019)
Aim The effects of past climatic shifts remain enigmatic for the Amazon region, especially for islands of savanna within the tropical forest known as “Amazonian savannas” ( AS ). These disjunct savanna areas share many plant and animal species with the Cerrado biome in central Brazil (the CC ), fuelling debate over historical connections. We evaluate hypothesized corridors between the CC and the AS , and specifically investigate whether a history of isolation versus recent connections is supported by genetic tests. Location Cerrado and Amazon biomes. Taxon Two woody plant species: Byrsonima coccolobifolia and B. crassifolia (Malpighiaceae). Methods Analyses of genomic data ( SNP s from more than 4,500 loci) in 28 populations, as well as chloroplast DNA (cp DNA ), were used to test for parallel geographic structuring between the CC and AS —an expected structure if putative corridors provided regional connections between different areas of the CC and AS , and divergence times between the CC and AS were estimated using a composite‐likelihood method based on the site frequency spectrum. Results Genomic data, in contrast with cp DNA , generally show strong, concordant genetic structure between the CC and AS in both species, rather than regional grouping of CC with AS populations. In addition, divergence between the CC and AS predates the Last Glacial Maximum. Main conclusions Our results suggest the AS have remained relatively isolated from the CC even though the strong structure of genomic variation is not shared by cp DNA . We note that past evidence of putative corridors between the CC and AS based solely on cp DNA should be interpreted cautiously since the lack of structure may reflect limited genetic resolution rather than gene flow. As such, the uniqueness of AS may be more pronounced than previously thought, highlighting the importance of protecting these highly threatened areas.

Breaking out of biogeographical modules: range expansion and taxon cycles in the hyperdiverse ant genus Pheidole - Evan P. Economo; Eli M. Sarnat; Milan Janda; Ronald Clouse; Pavel B. Klimov; Georg Fischer; Benjamin D. Blanchard; Lizette N. Ramirez; Alan N. Andersen; Maia Berman; Benoit Guénard; Andrea Lucky; et al. (Journal of Biogeography, 2015)
Aim We sought to reconstruct the biogeographical structure and dynamics of a hyperdiverse ant genus, Pheidole, and to test several predictions of the taxon cycle hypothesis. Using large datasets on Pheidole geographical distributions and phylogeny, we (1) inferred patterns of biogeographical modularity (clusters of areas with similar faunal composition), (2) tested whether species in open habitats are more likely to be expanding their range beyond module boundaries, and (3) tested whether there is a bias of lineage flow from high‐ to low‐diversity areas. Location The Old World. Methods We compiled and jointly analysed a comprehensive database of Pheidole geographical distributions, the ecological affinities of different species, and a multilocus phylogeny of the Old World radiation. We used network modularity methods to infer biogeographical structure in the genus and comparative methods to evaluate the hypotheses. Results The network analysis identified eight biogeographical modules, and a suite of species with anomalous ranges that are statistically more likely to occur in open habitat, supporting the hypothesis that open habitats promote range expansion. Phylogenetic analysis shows evidence for a cascade pattern of colonization from Asia to New Guinea to the Pacific, but no ‘upstream’ colonization in the reverse direction. Main conclusions The distributions of Pheidole lineages in the Old World are highly modular, with modules generally corresponding to biogeographical regions inferred in other groups of organisms. However, some lineages have expanded their ranges across module boundaries, and these species are more likely to be adapted to open habitats rather than interior forest. In addition, there is a cascade pattern of dispersal from higher to lower diversity areas during these range expansions. Our findings are consistent with the taxon cycle hypothesis, although they do not rule out alternative interpretations.

Ratification vote on taxonomic proposals to the International Committee on Taxonomy of Viruses (2015) - M. J. Adams; E. J. Lefkowitz; A. M. Q. King; D. H. Bamford; M. Breitbart; A. J. Davison; S. A. Ghabrial; A. E. Gorbalenya; N. J. Knowles; P. Krell; R. Lavigne; D. Prangishvili; et al. (Archives of Virology, 2015)

A Comparison of In Situ Constant and Falling Head Permeameter Tests to Assess the Distribution of Clogging Within Horizontal Subsurface Flow Constructed Wetlands - A. Pedescoll; P. R. Knowles; P. Davies; J. García; J. Puigagut (Water, Air, & Soil Pollution, 2012)

CLT1 targets angiogenic endothelium through CLIC1 and fibronectin - Lynn M. Knowles; Gunjan Malik; Brian L. Hood; Thomas P. Conrads; Jan Pilch (Angiogenesis, 2012)

Comparative sequence analysis of representative foot-and-mouth disease virus genomes from Southeast Asia - Nor Faizah Abdul-Hamid; Müge Fırat-Saraç; Alan D. Radford; Nick J. Knowles; Donald P. King (Virus Genes, 2011)

Interpreting seawater temperature range using oxygen isotopes and zooid size variation in Pentapora foliacea (Bryozoa) - T. Knowles; M. J. Leng; M. Williams; P. D. Taylor; H. J. Sloane; B. Okamura (Marine Biology, 2010)

Ovine progressive pneumonia provirus levels associate with breed and Ovar-DRB1 - Lynn M. Herrmann-Hoesing; Stephen N. White; Michelle R. Mousel; Gregory S. Lewis; Donald P. Knowles (Immunogenetics, 2008)

Common polymorphisms of ALOX5 and ALOX5AP and risk of coronary artery disease - Themistocles L. Assimes; Joshua W. Knowles; James R. Priest; Analabha Basu; Kelly A. Volcik; Audrey Southwick; Holly K. Tabor; Jaana Hartiala; Hooman Allayee; Megan L. Grove; Raymond Tabibiazar; Stephen Sidney; et al. (Human Genetics, 2008)

Genetic characterization and molecular epidemiology of foot-and-mouth disease viruses isolated from Afghanistan in 2003–2005 - Kate R. Schumann; Nick J. Knowles; Paul R. Davies; Rebecca J. Midgley; Jean-Francois Valarcher; Abdul Quader Raoufi; Thomas S. McKenna; William Hurtle; James P. Burans; Barbara M. Martin; Luis L. Rodriguez; Tammy R. Beckham (Virus Genes, 2008)

Genomic analysis of Ovis aries (Ovar) MHC class IIa loci - Lynn M. Herrmann-Hoesing; Stephen N. White; Lowell S. Kappmeyer; David R. Herndon; Donald P. Knowles (Immunogenetics, 2008)

Willamette: A Chipping Cultivar with High Yield and Specific Gravity, Low Incidence of Hollow Heart and Brown Center, and Suitability for Fresh-Market Usage - A. R. Mosley; S. Yilma; D. C. Hane; S. R. James; K. A. Rykbost; C. C. Shock; S. L. Love; D. L. Corsini; J. J. Pavek; R. E. Thornton; B. A. Charlton; E. P. Eldredge; et al. (American Journal of Potato Research, 2008)

Temperature-induced changes in potato processing quality during storage are modulated by tuber maturity - Edward P. Driskill; Lisa O. Knowles; N. Richard Knowles (American Journal of Potato Research, 2007)

Within‐population variation in prevalence and lineage distribution of avian malaria in blue tits, Cyanistes caeruleus - MATTHEW J. WOOD; CATHERINE L. COSGROVE; TEDDY A. WILKIN; SARAH C. L. KNOWLES; KAREN P. DAY; BEN C. SHELDON (Molecular Ecology, 2007)
The development of molecular genetic screening techniques for avian blood parasites has revealed many novel aspects of their ecology, including greatly elevated diversity and complex host–parasite relationships. Many previous studies of malaria in birds have treated single study populations as spatially homogeneous with respect to the likelihood of transmission of malaria to hosts, and we have very little idea whether any spatial heterogeneity influences different malaria lineages similarly. Here, we report an analysis of variation in the prevalence and cytochrome b lineage distribution of avian malaria infection with respect to environmental and host factors, and their interactions, in a single blue tit ( Cyanistes caeruleus ) population. Of 11 Plasmodium and Haemoproteus cytochrome b lineages found in 997 breeding individuals, the three most numerous (pSGS1, pTURDUS1 and pBT7) were considered separately, in addition to analyses of all avian malaria lineages pooled. Our analyses revealed marked spatial differences in the prevalence and distribution of these lineages, with local prevalence of malaria within the population ranging from over 60% to less than 10%. In addition, we found several more complex patterns of prevalence with respect to local landscape features, host state, parasite genotype, and their interactions. We discuss the implications of such heterogeneity in parasite infection at a local scale for the study of the ecology and evolution of infectious diseases in natural populations. The increased resolution afforded by the combination of molecular genetic and geographical information systems (GIS) tools has the potential to provide many insights into the epidemiology, evolution and ecology of these parasites in the future.

Comprehensive characterization of skeletal tissue growth anomalies of the finger coral Porites compressa - Isabelle J. Domart-Coulon; Nikki Traylor-Knowles; Esther Peters; David Elbert; Craig A. Downs; Kathy Price; Joanne Stubbs; Shawn McLaughlin; Evelyn Cox; Greta Aeby; P. Randy Brown; Gary K. Ostrander (Coral Reefs, 2006)

Identification and phylogenetic analysis of 15 MHC class II DRB1 β1 expressed alleles in a ewe–lamb flock - Lynn M. Herrmann; Wendy C. Brown; Greg S. Lewis; Donald P. Knowles (Immunogenetics, 2005)

Bacterial community structure and function in a metal‐working fluid - Christopher J. Van Der Gast; Andrew S. Whiteley; Andrew K. Lilley; Christopher J. Knowles; Ian P. Thompson (Environmental Microbiology, 2003)
Summary The diversity of bacterial populations colonizing spatially and temporally separated samples of the same metal‐working fluid (MWF) formulation was investigated. Analyses were performed with a view to improve strategies for bioaugmentation of waste MWF in bioreactor systems and prevention of in‐use MWF biodeterioration in engineering workshops. Significantly, complementary phenotypic, genotypic and in situ methods revealed that the bacterial communities in operationally exhausted MWFs had low diversity and were similar in species composition from different locations and uses. Of the 179 bacterial isolates studied, only 11 genera and 15 species were identified using fatty acid methyl ester (FAME) analysis, with culture independent analyses by 16S rDNA denaturing gradient gel electrophoresis (DGGE) and fluorescent in situ hybridization being congruent with these FAME data. In order to gain some insight into functional role of detected populations, we correlated the MWF chemical composition and potential pollution load with bacterial abundance and community composition detected within samples.

Statistical Phylogeography - L. Lacey Knowles; Wayne P. Maddison (Molecular Ecology, 2002)

Statistical phylogeography - L. Lacey Knowles; Wayne P. Maddison (Molecular Ecology, 2002)

Substrate‐regulated cyanide hydratase ( chy ) gene expression in Fusarium solani : the potential of a transcription‐based assay for monitoring the biotransformation of cyanide complexes - M. Barclay; J. C. Day; I. P. Thompson; C. J. Knowles; M. J. Bailey (Environmental Microbiology, 2002)
Summary The fungus Fusarium solani detoxifies cyanide through induction of the cyanide hydratase gene activity ( chy ) in the presence of either KCN or the metal‐complexed cyanides, K 2 Ni(CN) 4 or K 4 Fe(CN) 6 , at pH 7.0 and 4.0 respectively. Sequence analysis of the chy gene identified primers for reverse transcriptase–polymerase chain reaction (RT–PCR)‐directed analysis of mRNA transcripts, which demonstrated that activity correlated to the substrate‐specific induction of gene expression. chy transcription was initiated 30–60 min after exposure of F. solani cultures to cyanide complexes. Maximum expression was detected within 4.5 h, after which chy mRNA synthesis declined below the limits of detection within 26 h. A lag period of ≈ 2 h, following initial transcription, was recorded before cyanide complexes were converted to formamide. mRNA transcripts of chy were not detected in the absence of cyanide or cyanide complexes. The presence of introns within the gene resulted in a difference in size of 100 bp for DNA compared with mRNA of the corresponding 5 ′ region. This size difference facilitated PCR detection of gene and transcript respectively. Comparisons of the predicted amino acid sequence of the F. solani chy gene and those of Gloeocerospora sorghi , Fusarium lateritium and Leptosphaeria maculans demonstrate that cyanide hydratase genes are highly conserved and of a similar evolutionary origin. These data predict that the functional assay described here to monitor the induction of chy gene expression and, potentially, cyanide degradation would be applicable to a variety of polluted environments.

Diagnosis of foot-and-mouth disease by RT-PCR: use of phylogenetic data to evaluate primers for the typing of viral RNA in clinical samples - S. M. Reid; N. P. Ferris; G. H. Hutchings; K. De Clercq; B. J. Newman; N. J. Knowles; A. R. Samuel (Archives of Virology, 2001)

Expression and immune recognition of SV40 Tag in transgenic mice that develop metastatic osteosarcomas - Ildiko Marton; Susan E. Johnson; Ivan Damjanov; Karen S. Currier; John P. Sundberg; Barbara B. Knowles (Transgenic Research, 2000)

Epicuticular waxes and regulation of ear wetting and pre-harvest sprouting in barley and wheat - R.W. King; P. von Wettstein-Knowles (Euphytica, 2000)

Nitrogen monoxide production and consumption in an organic soil - P. F. Dunfield; R. Knowles (Biology and Fertility of Soils, 1999)

Lactation-induced WAP-SV40 Tag Transgene Expression in C57BL/6J Mice Leads to Mammary Carcinoma - Margaret R. Hüsler; Kristin A. Kotopoulis; John P. Sundberg; Barabara J. Tennent; Sabine V. Kunig; Barabara B. Knowles (Transgenic Research, 1998)

Structure and mechanism of galactose oxidase: catalytic role of tyrosine 495 - Mark P. Reynolds; Andrew J. Baron; Carrie M. Wilmot; Elinor Vinecombe; Conrad Stevens; Simon E. V. Phillips; Peter F. Knowles; M. J. McPherson (JBIC Journal of Biological Inorganic Chemistry, 1997)

Biological oxidation of nitric oxide in a humisol - P. F. Dunfield; Roger Knowles (Biology and Fertility of Soils, 1997)

The cellulase genes of Trichoderma - Jonathan Knowles; Pivi Lehtovaara; Merja Penttil; Tuula Teeri; Anu Harkki; Irma Salovuori (Antonie van Leeuwenhoek, 1987)